2013
DOI: 10.2337/dc13-0669
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Stroke According to Presence of Diabetic Nephropathy and Severe Diabetic Retinopathy in Patients With Type 1 Diabetes

Abstract: OBJECTIVEType 1 diabetes is associated with a markedly increased risk of stroke, but only a few studies on the incidence of stroke in type 1 diabetes exist. Therefore, we assessed the incidence of stroke in patients with type 1 diabetes and studied the impact of diabetic nephropathy (DN) and severe diabetic retinopathy (SDR) on this risk.RESEARCH DESIGN AND METHODSWe studied 4,083 patients with type 1 diabetes from the Finnish Diabetic Nephropathy Study. Mean age was 37.4 ± 11.8 years, duration of diabetes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 28 publications
6
64
1
3
Order By: Relevance
“…The study design is an observational follow-up study, and a detailed description of the research design and population has previously been reported. 8 At baseline, both the attending physicians and the patients themselves completed questionnaires regarding the patient's medical condition, medical history, and lifestyle. For the present study, we included all the 4083 patients with type 1 diabetes mellitus in the FinnDiane database without a history of stroke at baseline, as well as with complete information on stroke during follow-up available.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study design is an observational follow-up study, and a detailed description of the research design and population has previously been reported. 8 At baseline, both the attending physicians and the patients themselves completed questionnaires regarding the patient's medical condition, medical history, and lifestyle. For the present study, we included all the 4083 patients with type 1 diabetes mellitus in the FinnDiane database without a history of stroke at baseline, as well as with complete information on stroke during follow-up available.…”
Section: Methodsmentioning
confidence: 99%
“…We have earlier shown that both the severity of diabetic nephropathy (DN) and the presence of severe diabetic retinopathy (SDR) increase the risk of any stroke, ischemic stroke, lacunar infarction, and hemorrhagic stroke. 8 However, comprehensive studies on independent risk factors for each subtype of stroke are still missing.Therefore, we aimed to study the independent risk factors for stroke, and also for the subtypes ischemic stroke, lacunar Background and Purpose-Despite the fact that patients with type 1 diabetes mellitus have a markedly increased risk of experiencing a stroke, independent risk factors for stroke and its subtypes in these patients have remained unclear. Methods-A total of 4083 patients with type 1 diabetes mellitus from the Finnish Diabetic Nephropathy (FinnDiane) Study, without a history of stroke at baseline, were included.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of retinopathy increases the risk of stroke [22] . Severe diabetic retinopathy was common in the "Golden Years Cohort" [10] .…”
Section: Type 1 Diabetes and The Metabolic Syndromementioning
confidence: 99%
“…Overall, there was a significant or macroalbuminuria is a significant risk factor for CAD, cardiovascular mortality and all cause mortality, and there is a strong independent relationship between albuminuria and CAD (Table 1) [7] . The occurrence of stroke in subjects with type 1 diabetes is also increased by the presence of nephropathy [microalbuminuria: HR = 3.2 (1.9-5.6), macroalbuminuria: HR = 4.9 (2.9-8.2), End Stage Renal Disease: HR = 7.5 (4.2-13.3)] [22] . The DCCT/EDIC Study showed a sustained effect of good glycaemic control [23] on the reduction in albumin excretion 7 years after the conclusion of the DCCT study, with an 83% risk reduction in those patients initially treated with intensive therapy, confirming the concept of "metabolic memory".…”
Section: Type 1 Diabetes and The Metabolic Syndromementioning
confidence: 99%